A fenomenologia do éthos: intuições éticas a partir da obra de Lima Vaz - Perin, Ricardo José (2022)
The research circumscribes, in the light of the work of Henrique Cláudio de Lima Vaz (1921-2002), an influential Jesuit thinker, the theme of the phenomenology of ethos. To this end, the study is primarily concerned with reconstituting some important reflective steps of this thematic axis from a multidisciplinary perspective, especially towards Psychoanalysis. The first step consists in specifying what, in Lima Vaz's terms, is understood by phenomenology in order to better situate the dimension of ethos as a transcription from the Greek notion of physis in classical antiquity. The second aims to reconstitute, from this transcription, the triple mutual figuration between the individual, the conflict and the culture. The third is the anthropological understanding, in the course of this event in modernity and, with it, a diagnosis of moral conscience in a state of crisis. The last great moment proposes to establish the link between Éthos and Psychoanalysis through three fundamental ethical intuitions that are mirrored in this broader picture: i) the capillary inscription of the psychic as a primordial sphere; ii) the articulation between Ethics and Psychoanalysis within the clinical experience and iii) the return to the infantile ethos as an archaeological dimension in the midst of the new configurations of personality formation at the turn of the new century. This culmination of the investigation carried out here turns, above all, to a whole psychoanalytic-hermeneutic work, of evidently ethical concern, in the sense of better demarcating the origins of the psychic subject. Finally, the research advocates the thesis that the work of Lima Vaz establishes a dialectical movement, phenomenological by definition, capable not only of dialoguing with Psychoanalysis, but also of relocating the genesis of ethos as a background without which there is no an ethics of living capable of responding to contemporary demands, that is, to the challenges imposed by an increasingly plural and unequal society.